Organized Crime, Corruption and Punishment - Maurice Kugler; Thierry Verdier; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2003)
We analyze an oligopoly model in which differentiated criminal organizations globally compete on criminal activities and engage in local corruption to avoid punishment. When law enforcers are sufficiently well-paid, difficult to bribe and corruption detection highly probable, we show that increasing policing or sanctions effectively deters crime. However, when bribing costs are low, that is badly-paid and dishonest law enforcers work in a weak governance environment, and the rents from criminal activity relative to legal activity are sufficiently high, we find that increasing policing and sanctions can generate higher crime rates. In particular, the relationship between the traditional instruments of deterrence, namely intensification of policing and increment of sanctions, and crime is nonmonotonic. Beyond a threshold, increases in expected punishment induce organized crime to corruption, and ensuing impunity leads too higher rather than lower crime.
Keywords: K42; L13; 330; Deterrence; Organized Crime; Corruption; Oligopoly; Free Entry; Organisierte Kriminalität; Korruption; Oligopol; Neue politische Ökonomie; Theorie; Rechtsdurchsetzung